2010
DOI: 10.1111/j.1745-7599.2010.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

CE ARTICLE: Recognizing and treating upper extremity lymphedema in postmastectomy/lumpectomy patients: A guide for primary care providers

Abstract: Purpose: To provide an overview of the lymphatics, physiology of lymphedema (LE), incidence, risks, and costs as well as a guide for the primary care provider on how to recognize the symptoms of LE, a review of current published treatment recommendations, and advice about making a referral to appropriate LE specialists. Data sources: Selected studies on diagnosing and treating LE in breast cancer patients following mastectomy/lumpectomy and evidence-based treatment guidelines. Conclusions: LE is the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
(93 reference statements)
0
13
0
5
Order By: Relevance
“…20,21 In our study, 12 of 38 patients (31.6%) had an infection at least once and at the most six times. Their increased frequency of infection increased the development of fibrotic tissue.…”
Section: Upper Extremity Functions In Patients With Lymphedemamentioning
confidence: 96%
See 2 more Smart Citations
“…20,21 In our study, 12 of 38 patients (31.6%) had an infection at least once and at the most six times. Their increased frequency of infection increased the development of fibrotic tissue.…”
Section: Upper Extremity Functions In Patients With Lymphedemamentioning
confidence: 96%
“…33 Radiation therapy caused destruction of the related tissues leading to fibrosis, which then leads to the restriction of shoulder movements. 20 Ozçinar et al identified statistically significant limitations in shoulder flexion, abduction, and internal and external rotation movements in the early period of breast cancer treatment (week 1). They also showed a significant limitation of the ongoing internal rotation measurements by 9-12 months after surgery.…”
Section: Upper Extremity Functions In Patients With Lymphedemamentioning
confidence: 97%
See 1 more Smart Citation
“…This relationship is well corroborated by existing literature. [18][19][20][21] Although neither the scope of this study nor its design were intended to critically analyze the influence of breast reconstruction on lymphedema development, breast reconstruction did not appear to affect risk in the present study. Prior research indicates an improvement in existing lymphedema and reduced the risk of primary lymphedema development with delayed breast reconstruction after oncologic resection [22][23][24] ; more recently, immediate reconstruction has also been reported to decrease risk.…”
Section: Risk Factors For Lymphedemamentioning
confidence: 99%
“…The prevalence BCRL is between 12% and 28% (Meric et al, 2002;Ozaslan & Kuru, 2004;Clark, Sitzia, & Harlow, 2005). This variation can be explained in part by differences in the criteria used to define and diagnosis lymphedema (Quirion, 2010;Jain, Danoff, & Paul, 2010;Petrek & Heelan, 1998).…”
Section: Introductionmentioning
confidence: 99%